How Useful Photography is in Sociological Researches on Ethnic Identity Studies? - Pandey, Krishna P (Himalayan Journal of Sociology and Anthropology, 2017)
The origins of photography and sociology date back almost at the same time, but the relationship between them was not as intimate as it was to be. Sociologists refrained from using photography as a method in their researches until the importance of qualitative research was realized. Debate is still going on whether photographs expose total social reality or just provide the possibilities of subjective interpretations in the form of partial truths. Anthropologists, to some extent, are ahead in using photographs in their ethnographic works from early years. The essay deals photography only as a means of sociologists’ engagement with issues of identity formation with reference to ethnicity. The narrative potentiality of photography, which is crucial to uncover the meanings embedded in peoples’ struggles for identity, becomes its strength to claim as a research tool in qualitative research in sociology. Furthermore, enriched with meanings photographs bring subjectivists and constructivists closer to the discipline of photography. The importance of photography in constructing meanings through grounded theory method research on ethnic identity concerns of various cultural groups, largely in south Asia, cannot be underscored since the photographic practice has already made its claim for the place in qualitative sociology and anthropology. Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), Page: 75-95